EVALUATING COMPETENCY-BASED RECRUITMENT AND TRAINING EFFECTIVENESS IN WEST JAVA'S PUBLIC SECTOR HUMAN RESOURCE MANAGEMENT - Seno Djulian Saputra (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This article evaluates the effectiveness of competency-based recruitment and training practices within the public sector human resource management in West Java, Indonesia. Utilizing a qualitative approach, this study conducts a comprehensive literature review to analyze existing frameworks and best practices in competency-based human resource management. The findings highlight the significance of aligning recruitment processes with organizational competencies to enhance workforce quality and performance. Additionally, the study identifies key challenges faced by public sector organizations in implementing these practices, including limited resources, bureaucratic obstacles, and a lack of awareness regarding competency frameworks. The research emphasizes the importance of tailored training programs that not only address the specific competencies required for various roles but also facilitate continuous professional development. By fostering a culture of competency-based management, public sector organizations in West Java can improve employee engagement and service delivery. The article concludes with practical recommendations for policymakers and human resource managers to enhance the effectiveness of recruitment and training processes, ultimately contributing to better public service outcomes. This study serves as a foundational reference for future research on competency-based human resource management in the region, advocating for a strategic shift towards more effective human resource practices in the public sector.